2023
DOI: 10.1001/jamanetworkopen.2022.52061
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Wait Times for Care Among US Veterans by Race and Ethnicity

Abstract: ImportancePrior studies indicate that Black and Hispanic vs White veterans wait longer for care. However, these studies do not capture the COVID-19 pandemic, which caused care access disruptions, nor implementation of the US Department of Veterans Affairs (VA) Maintaining Internal Systems and Strengthening Integrated Outside Networks Act (MISSION), which is intended to improve care access by increasing veterans’ options to use community clinicians.ObjectiveTo determine whether wait times increased differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…However, Black and Hispanic Veterans had, on average, longer wait times for all services 16. In a recently published paper using more current data, we found that wait time for Black and Hispanic Veterans increased more than White Veterans’ wait time during the COVID pandemic 17…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…However, Black and Hispanic Veterans had, on average, longer wait times for all services 16. In a recently published paper using more current data, we found that wait time for Black and Hispanic Veterans increased more than White Veterans’ wait time during the COVID pandemic 17…”
mentioning
confidence: 54%
“…16 In a recently published paper using more current data, we found that wait time for Black and Hispanic Veterans increased more than White Veterans' wait time during the COVID pandemic. 17 Our overall goal in this study was to illustrate the use and value of the 2-stage Kitagawa decomposition to partition disparities in outcomes into within-facility and between-facility differences and to identify those facilities that contribute the most to each component. This study received a nonhuman subject research determination from the VA Boston Institutional Review Board.…”
mentioning
confidence: 99%
“…41,43 We used insurance type as a proxy for health care access. In addition to insurance type, other financial and physical barriers exist, such as the availability of appointments with primary and specialty care providers, 57 the distance between minority populations and needed care-as may occur with residential segregation, 58,59 and inequities in paid family medical leave. 60 Veterans receiving care within the Veterans Health Administration have reduced mortality for patients identifying as Black versus White.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, disparities persist in health and health care due to nonclinical differences such as race and sex. [2][3][4][5][6] Understanding veteran experiences is an essential part of the VHA action plan for advancing health equity. 7 Veteran experiences must be contextualized within the realities of the contemporary sociopolitical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Equitable care is a major tenet of the Veterans Health Administration (VHA) mission . However, disparities persist in health and health care due to nonclinical differences such as race and sex . Understanding veteran experiences is an essential part of the VHA action plan for advancing health equity…”
Section: Introductionmentioning
confidence: 99%